Effect of elevated temperatures on concrete incorporating ferronickel slag as fine aggregate - Saha, A.; Sarker, Prabir; Majhi, S. (John Wiley and Sons Ltd., 2018)
This study evaluates the effect of elevated temperature exposure on concrete incorporating ferronickel slag (FNS) as a replacement of natural sand. Concrete cylinders were exposed up to 800°C, and the changes in compressive strength, mass, ultrasonic pulse velocity (UPV), and microstructure were investigated. The concretes containing up to 100% FNS aggregate showed no spalling and similar cracking to that of the concrete using 100% natural sand. For exposures up to 600°C, the residual strengths of concretes containing 50% FNS were 7% to 10% smaller than the concrete with 100% sand. Use of 30% fly ash as cement replacement improved residual strength by pozzolanic reaction for exposures up to 600°C. An equation has been found from the correlation between residual strength and UPV. Therefore, UPV can be used as a nondestructive test to estimate the extent of postfire damage and residual strength of concrete incorporating FNS aggregate and fly ash.